3,3-Bis(2-hydroxyethyl)-1-(4-nitrobenzoyl)thiourea: crystal structure, Hirshfeld surface analysis and computational study - Tan, Sang Loon *; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2020)
In the title compound, C12H15N3O5S, a trisubstituted thiourea derivative, the central CN2S chromophore is almost planar (r.m.s. deviation = 0.018 A˚ ) and the pendant hydroxyethyl groups lie to either side of this plane. While to a first approximation the thione-S and carbonyl-O atoms lie to the same side of the molecule, the S—C—N—C torsion angle of 47.8 (2) indicates a considerable twist. As one of the hydroxyethyl groups is orientated towards the thioamide residue, an intramolecular N—H...O hydrogen bond is formed which leads to an S(7) loop. A further twist in the molecule is indicated by the dihedral angle of 65.87 (7) between the planes through the CN2S chromophore and the 4-nitrobenzene ring. There is a close match between the experimental and gas-phase, geometry-optimized (DFT) molecular structures. In the crystal, O— H...O and O—H...S hydrogen bonds give rise to supramolecular layers propagating in the ab plane. The connections between layers to consolidate the three-dimensional architecture are of the type C—H...O, C—H...S and nitroO...π. The nature of the supramolecular association has been further analysed by a study of the calculated Hirshfeld surfaces, non-covalent interaction plots and computational chemistry, all of which point to the significant influence and energy of stabilization provided by the conventional hydrogen bonds.